Multicompartment Synthetic Vesicles for Artificial Cell Applications - Shin, Jooyong; Jang, Yeongseon (ACS applied engineering materials, 2024)
This review explores the cutting-edge development of multicompartment synthetic vesicles designed for artificial cell applications, drawing inspiration from the complex compartmentalization inherent in living cells. It delves into the recent advancements in engineering vesicles equipped with both membranous and membraneless organelles (vesicles-in-vesicles and coacervates-in-vesicles), offering a detailed examination of the methodologies and materials employed. This paper highlights the critical role of these multicompartment vesicles in simulating cellular microenvironments and functions, facilitating the spatial and temporal segregation of biochemical processes, such as signal transduction, gene expression, ATP synthesis, and energy production. Moreover, this review outlines potential future directions, emphasizing the importance of these vesicles in the evolution of artificial cells with a focus on their application in creating more sophisticated biomimetic systems.